The Influence of Ushul Fiqh Training and Academic Involvement on Critical Thinking Disposition - Khalifah Maulidiyah; Ilzam Dhaifi (Program Pascasarjana Universitas Ibrahimy, 2024)
Education in the era of dynamic information demands the development of critical thinking skills, which are reflected in critical thinking disposition as a tendency to think reflectively and rationally. In the context of Ma’had Aly, the complexity of Ushul Fikih studies requires learning models that encourage students’ intellectual engagement. One such model is Ushul Fikih Training based on guided inquiry, which is assumed to be closely related to academic engagement. However, empirical studies linking these three variables remain limited. This study aims to examine the influence of guided inquiry (X1) and academic engagement (X2) on students’ critical thinking disposition (Y). Using a quantitative approach, the research was conducted at Ma’had Aly Salafiyah Syafi’iyah at the Marhalah Ula level. Data were analyzed using multiple linear regression. The results indicate that guided inquiry and academic engagement have a significant effect on critical thinking disposition, both independently and in combination. These variables account for 17.8% of students’ critical thinking disposition, while the remaining 82.2% is explained by factors outside this research model.